The Application of Developed Delone & McLean Method to Analyze The Success and Effectiveness of Alfagift Application Among Big Cities' Users in Indonesia - Pramudito, Dendy K; Arijanti, Susi; Akbar, Zulfikri; Haribowo, Rio; Diawati, Prety (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to find out how successful application use is and what factors influence the successful use of online shopping applications. This research uses quantitative methods. Users of online shopping applications in Jabodetabek were given a questionnaire via Google Form as part of the data collection method used in this study. Users of online shopping apps made up the study's population. Purposive sampling was the method used to choose the study's sample. In this study, a sample of one hundred respondents was used. The two types of data analysis are statistical analysis and demographic analysis. The results of the conducted research support the notion that the presence of online shopping applications is beneficial, and that user perceptions play a significant role in the success of an application's use. Respondents can shop online with convenience and utility thanks to the services offered by online shopping applications. User satisfaction with net benefits is the most significant factor, according to the path coefficient and t-test values. This indicates that consumers are happy with the online shopping app and are inclined to accept the advantages it provides. Consumers believe that an element that can raise the net benefit value of online shopping applications is user satisfaction. According to the path coefficient and t-test values, service quality is the factor that has the least impact on users' perceptions of its usefulness. This indicates that consumers believe the usefulness value they perceive from online shopping applications cannot be enhanced by the quality of those services. So, improvements need to be made so that the success of using the application increases.